Salt application as an effective measure to control ruderal invaders threatening endangered halophytic plant species. Issue 3 (20th November 2012) - Khan, Zeeba; Albrecht, Matthias; Traveset, Anna; Middleton, Beth
Abstract Questions How does salinity affect germination, seedling performance and survival of the critically endangered Limonium barceloi, compared to ruderal species invading its salt marsh habitat? Is salt application an effective management tool for controlling invaders and favouring endangered halophytes? Location Ses Fontanelles, Mallorca, Balearic Islands, Spain. Methods The germination of seeds of L. barceloi and nine ruderal species was tested in five salinity levels (0–37 g·L−1), and also in freshwater after a pre‐treatment with seawater. The ruderal study species were: Asphodelus fistulosus, Avena barbata, Geranium molle, Hypochoeris achyrophorus, Oryzopsis miliacea, Plantago coronopus, Reichardia picroides, Sonchus asper and Sonchus tenerrimus. Two salt concentration levels (18 and 37 g·L−1) were applied twice monthly, weekly or twice weekly to examine the effect of salt irrigation schemes on the performance and seedling survival of L. barceloi compared to two of the principal species invading these salt marshes, S. tenerrimus and A. fistulosus. Results Germination of L. barceloi and most ruderal species was highest at low salinity (0–8 g·L−1). Seeds of L. barceloi, A. fistulosus and S. tenerrimus were also able to germinate at the highest salinity level, in contrast to the other species. Germination in freshwater after seawater pre‐treatment was highest in L. barceloi (72 ± 6%). Seedling performance and survival of A. fistulosus and S. tenerrimus decreased with frequency and concentration of the salt treatment. An application of 37 g·L−1 salt twice a week reduced seedling survival of A. fistulosus and S. tenerrimus by 83.3 and 91.6%, respectively. In contrast, 100% of the L. barceloi seedlings survived and showed similar performance among treatments. Conclusions Limonium barceloi had higher seedling growth and survival than ruderal invaders when salinity levels were high (37 g·L−1). Nevertheless, at lower salinity, ruderal species may germinate and grow better and thus salinity level changes may represent a threat to the survival of this critically endangered species. Although further field testing is required, our experiments suggest that salt application could be an effective measure to protect L. barceloi and other endangered halophytic plant species from less salt‐tolerant invaders.